Money Talks: The Influence of Economic Crisis on Global Governance - Albassam, Bassam A. (Mediterranean Journal of Social Sciences, 2012)
The economic crisis has had an influence on all aspects of life, from economic to social life, from national security togovernance, and from politics to sports. The consequences of the economic crisis of 2008 could shape the future of globalgovernance. Also, the appearance of new players in influencing and restructuring the global political system, such as private andstate-owned Transnational Corporations (TNCs), makes us rethink the ways in which we need to approach human developmentissues such as fighting corruption, supporting human rights and higher living standards, and maintaining good governancepractices worldwide. Thus, this article addresses the influence of the economic crisis of 2008 on formal and informal governance.The focus of this article is addressing the increasing of economic and political power of TNCs, especially state-owned TNCs, andtheir influence on the global political system. The conclusion reached is that International Organizations (IOs), civil societyorganizations, people, and even TNCs need to work together to reorganize the political scene with new international agreementsand IOs, because institutions and international agreements that initiated after WWII are not working affectively anymore.